2012
DOI: 10.1590/s0100-06832012000500026
|View full text |Cite
|
Sign up to set email alerts
|

Changes in soil acidity and organic carbon in a sandy typic hapludalf after medium-term pig-slurry and deep-litter application

Abstract: SUMMARYSuccessive applications of liquid swine waste to the soil can increase the contents of total organic carbon and nutrients and change acidity-related soil chemical properties. However, little information is available on the effects of swine waste application in solid form, as of swine deep-litter. The objective of this study was to evaluate alterations of organic carbon and acidity-related properties of a soil after eight years of pig slurry and deep-litter application. In the eighth year of a field expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
30
2
10

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 22 publications
5
30
2
10
Order By: Relevance
“…However, this study also found that the pH may decrease or remain unaffected, depending on the chemical functional group, rate of addition, decomposition, and the initial soil pH. The increase in pH in the pasture soil was also previously attributed to animal excreta (Haynes &Williams, 1992;Shand & Coutts, 2006;Brunetto et al, 2012).…”
Section: Resultssupporting
confidence: 62%
“…However, this study also found that the pH may decrease or remain unaffected, depending on the chemical functional group, rate of addition, decomposition, and the initial soil pH. The increase in pH in the pasture soil was also previously attributed to animal excreta (Haynes &Williams, 1992;Shand & Coutts, 2006;Brunetto et al, 2012).…”
Section: Resultssupporting
confidence: 62%
“…Soil pH decreased with successive application of fertilizers, a process enhanced in soils receiving urea or materials containing urine, such as PS, due to the protons release during the oxidation of N; on the other hand, higher carbonate content in DL promotes consumption of H + dissolved in the soil, leading to pH increases (BRUNETTO et al, 2012). In this study, pH of DL treatment was similar to the control soil, with values around 6.0.…”
Section: Resultssupporting
confidence: 47%
“…Disposal of animal manure usually involves aerobic composting and anaerobic fermentation [2]. Pig slurry (PS) is primarily used as fertilizer in agricultural production to provide nutrients such as nitrogen (N), phosphorus (P), and potassium (K) to crops [3][4][5][6]. Tao et al [7] found that applying PS at 60-120 m 3¨h m´2 instead of chemical fertilizer at 30-60 kg N¨hm´2 during winter, at the panicle formation stage, could meet the high nitrogen demand utilization efficiency of wheat.…”
Section: Introductionmentioning
confidence: 99%